2012
DOI: 10.4251/wjgo.v5.i4.71
|View full text |Cite
|
Sign up to set email alerts
|

Current oncologic applications of radiofrequency ablation therapies

Abstract: Radiofrequency ablation (RFA) uses high frequency alternating current to heat a volume of tissue around a needle electrode to induce focal coagulative necrosis with minimal injury to surrounding tissues. RFA can be performed via an open, laparoscopic, or image guided percutaneous approach and be performed under general or local anesthesia. Advances in delivery mechanisms, electrode designs, and higher power generators have increased the maximum volume that can be ablated, while maximizing oncological outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 66 publications
0
51
0
2
Order By: Relevance
“…Radiofrequency ablation (RFA) has been increasingly accepted as a potentially promising nephron‐sparing, minimally invasive therapeutic option for patients with small localized renal masses. In addition, RFA as a primary or adjuvant treatment modality has been widely used in solid tumors such as hepatocellular carcinoma, lung cancer, breast cancer, and RCC [7]. In 1997, Zlotta et al [8] reported the first clinical use of renal RFA for the treatment of localized renal masses.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency ablation (RFA) has been increasingly accepted as a potentially promising nephron‐sparing, minimally invasive therapeutic option for patients with small localized renal masses. In addition, RFA as a primary or adjuvant treatment modality has been widely used in solid tumors such as hepatocellular carcinoma, lung cancer, breast cancer, and RCC [7]. In 1997, Zlotta et al [8] reported the first clinical use of renal RFA for the treatment of localized renal masses.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, minimal or non‐invasive ablation could offer an interesting option for tumor treatment, in order to avoid the risk of complications related to surgery and to optimize the cosmetic outcome, reducing patient discomfort. Furthermore, ablative treatments could be used to control local tumor growth, palliate symptoms, and improve survival in patients with poor health who are not candidates for surgical resection …”
mentioning
confidence: 99%
“…However, it has yet to be proven equivalent to surgical resection in randomized control trials since studies comparing the two treatments for resectable disease have yet to be performed [57]. Patients who undergo RFA alone for metastatic lesions immediately adjacent to a hepatic vein have higher incidences of intrahepatic recurrence due to the well-documented ''heat-sink'' effect.…”
Section: Alternative Therapies To Surgerymentioning
confidence: 96%